José Ignacio Hualde, Antxon Olarrea y Erin O’Rourke (eds.), The handbook of hispanic linguistics. Wiley-Blackwell, Malden-Oxford-West Sussex, 2012; 898 pp. - Gil Burgoin, Carlos Ivanhoe (El Colegio de México, 2015)
Se reseña el libro: The handbook of hispanic linguistics